The Role of Information Technology in the Development of an Integrated Land Multimodal Transportation System - Nirwana, Kamilla Cahya; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Transportation in Indonesia faces challenges of congestion, high costs, and uneven infrastructure. Information technology is essential for developing an integrated multimodal land transportation system to improve efficiency, transparency, and data management. A systematic literature review (2010-2025) shows that IoT, GPS, ITS, real-time tracking, EDI, Big Data, and AI improve operational performance. Case studies reveal the great potential of IT, despite infrastructure, human resources, and interoperability constraints. Regulations support digitization, but more coordination and investment is needed. Recommendations include infrastructure improvement, human resource development, standardization, and collaboration among stakeholders for an efficient and sustainable transportation system. Optimal implementation of information technology will be key to the success of national transportation transformation.